Organometal Halide Perovskite Quantum Dot Light-Emitting Diodes - Deng, Wei; Xu, Xiuzhen; Zhang, Xiujuan; Zhang, Yedong; Jin, Xiangcheng; Wang, Liang; Lee, Shuit-Tong; Jie, Jiansheng (Advanced functional materials, 2016)
Organometal halide perovskites quantum dots (OHP‐QDs) with bright, color‐tunable, and narrow‐band photoluminescence have significant advantages in display, lighting, and laser applications. Due to sparse concentrations and difficulties in the enrichment of OHP‐QDs, production of large‐area uniform films of OHP‐QDs is a challenging task, which largely impedes their use in electroluminescence devices. Here, a simple dip‐coating method has been reported to effectively fabricate large‐area uniform films of OHP‐QDs. Using this technique, multicolor OHP‐QDs light‐emitting diodes (OQ‐LEDs) emitting in blue, blue‐green, green, orange, and red color have been successfully produced by simply tuning the halide composition or size of QDs. The blue, green, and red OQ‐LEDs exhibited, respectively, a maximum luminance of 2673, 2398, and 986 cd m−2 at a current efficiency of 4.01, 3.72, and 1.52 cd A−1, and an external quantum efficiency of 1.38%, 1.06%, and 0.53%, which are much better than most LEDs based on OHP films. The packaged OQ‐LEDs show long‐term stability in air (humidity ≈50%) for at least 7 d. The results demonstrate the great potential of the dip‐coating method to fabricate large‐area uniform films for various QDs. The high‐efficiency OQ‐LEDs also demonstrate the promising potential of OHP‐QDs for low‐cost display, lighting, and optical communication applications. Organometal halide perovskite quantum dot (OHP‐QDs)‐based light‐emitting diodes (LEDs) are developed using a simple dip‐coating method. The OHP‐QDs‐based LEDs show multicolor emission from blue, green to red by tuning the composition or size of the OHP‐QDs. The packaged devices also exhibit robust stability under continuous bias in air for at least 7 d.